The biology and some population parameters of the grasshopper, Ronderosia bergi, under laboratory conditions - Mariottini, Yanina (2010)
Some biological and population parameters of Ronderosia bergi (Stl) (Orthoptera: Acrididae: Melanoplinae) were estimated by monitoring five cohorts of the first generation (F1) of individuals born in captivity from grasshoppers collected in the South of Misiones province, northeastern Argentina, and held under controlled conditions (30° C, 14:10 L:D, 40% RH). The mean embryonic development time was 40.6 ± 1.7 days. Five nymphal instars were recorded. Total duration of nymphal development was 30.8 ± 0.54 days. The mean lifespan of cohorts was 22.6 ± 0.7 weeks. The number of egg-pods per female was 7.6 ± 1.44, and the amount of eggs per egg-pod was 16.45 ± 0.85. Mean fecundity was 125 ± 5.83 eggs per female with an oviposition rate of 1.55 ± 0.57 eggs/female/day. Survivorship curves showed that mortality was concentrated in the final weeks of adulthood, and the life expectancy curve decreased accordingly. The population parameters estimated gave the following values: the net rate of reproduction (R0) was 46.75 ± 11.2, generation time (T) was 18.87 ± 1.67 weeks, duplication time (D) was 3.31 ± 0.34, the intrinsic rate of population growth (rm) was 0.21 ± 0.021 and the finite rate of population increase () was 1.24 ± 0.026. The reproductive values (Vx) indicated that the largest contribution of females to the subsequent generation was between weeks 15 and 25.